Systems analysis & design : - Marakas , George M (McGraw-Hill/Irwin, 2006)
This new book provides a concise text that teaches students first how to identify the problem, before analyzing and designing a solution. Marakas applies the structure method of SA&D with some coverage of object-oriented methods as an alternative. This text is accompanied by a web-based case simulation option that provides a realistic experience for students while automating administration for the instructor.